Sea Ice Topographic Retrieval in the Western Weddell Sea from TanDEM-X - Huang, Lanqing; Hajnsek, Irena (IGARSS 2023 - 2023 IEEE International Geoscience and Remote Sensing Symposium, 2023)
Single-pass interferometric synthetic aperture radar (InSAR) offers the potential to generate sea ice digital elevation models (DEMs) despite the inherent dynamics of sea ice. However, the accuracy of sea ice DEM generation from InSAR is hindered by the varying penetration bias across different types of ice. This paper presents a new scheme to generate sea ice DEMs (i.e., snow freeboard) across different ice types from TanDEM-X images. The proposed scheme is applied to generate a sea ice topographic map over a 630 km × 19 km area, revealing a spatial pattern of sea ice elevation. The highest elevations are observed near the Antarctica Peninsula (AP), with a rapid decrease in elevation within approximately 200km from the AP coastline, followed by a gradual increase towards the south.